Value-driven business process management the value-switch for lasting competitive advantage - Franz, Peter (McGraw-Hill, 2012)
Value-Driven Business Process Management gives business leaders in any industry the rationale and methods for using BPM to gain clarity on how their business operates and develop the ability to put new ideas into action quickly. Readers learn how to redirect their focus from a "method-and-tool" view of BPM to a more broadly informed view of BPM as a management approach and put it to practical use to initiate action within their organization.
Includes bibliographical references. - Description based on print version record
Keywords: Business -- Data processing -- Management; Management information systems; Value analysis (Cost control); Organizational effectiveness; Gestion; Informatique; Gestion; Systèmes d'information de gestion; Analyse de la valeur; Efficacité organisationnelle; Business; Data processing; Management; Commerce; Business & Economics; Marketing & Sales